Management of pharyngeal fistulas after anterior cervical spine surgery: a treatment algorithm for severe complications - Simon, Christian; Fürstenberg, Carl Hans; Eichler, Markus; Rohde, Stefan; Bulut, Cem; Wiedenhöfer, Bernd (Clinical spine surgery, 2017)
Study Design:This study is a retrospective database query to identify all anterior spinal approaches.Objectives:The objectives were to assess all patients with pharyngocutaneous fistulas (PCFs) after anterior cervical spine surgery.Summary of Background Data:Patients with the diagnosis of PCFs were
Gesehen am 19.08.2019